Possibility of paclitaxel to induce the stemness-related characteristics of prostate cancer cells - mutlu icduygu, fadime; Samli, Hale; Ozgoz, Asuman; Vatansever, Buse; Hekimler Ozturk, Kuyas; Akgun, Egemen (Wroclaw Medical University, 2021)
Drug resistance poses a crucial problem in the treatment of prostate cancer. Recent studies have shown that chemotherapy agents may cause cancer cells to acquire stem cell-like properties, resulting in drug resistance and, eventually, treatment failure.To evaluate whether long-term paclitaxel exposure causes an increase in the stem cell-like properties of prostate cancer cells.Paclitaxel-resistant PC-3 cells were generated from parental PC-3 cells by treating them with increasing concentrations of paclitaxel. The expression levels of the stem cell markers NANOG, C-MYC, CD44, and ABCG2 were evaluated using quantitative real-time polymerase chain reaction (RT-qPCR). A sphere formation assay was performed to test the potential of the cells to behave as stem cells, and a wound healing assay was carried out to evaluate migration ability of the cells.The expression levels of C-MYC and NANOG were significantly higher in paclitaxel-resistant PC-3 cells compared to the parental PC-3 cells. However, there was no significant increase in the expression of CD44 or ABCG2. In addition, the sphere-forming capacity and migration ability of resistant PC-3 cells were increased.The results of the current study indicate that paclitaxel exposure may increase the stem cell-like properties of PC-3 prostate cancer cells.
Keywords: Male; Paclitaxel; Humans; Prostatic Neoplasms; 3. Good health